Genomic bases of non-syndromic basal cell carcinoma: literature review - Daniel Sundfeld Spiga Real (Revista Brasileira de Cirurgia Plástica)
Introduction: Non-melanoma skin neoplasms represent the most frequent type in both sexes globally, with basal cell carcinoma being the most prevalent, representing 75 to 80% of cases. In Brazil, the number of new cases expected for the triennium 2020-2022 will be 83,770 in men and 93,160 in women, corresponding to an estimated risk of 80.12 new cases for 100,000 men and 86.65 new cases for 100,000 women. This data demonstrates the great importance of genomic knowledge in the genesis of sporadic basal cell carcinoma. Objective: To describe the main genes and molecular markers involved in the predisposition and pathogenesis of non-syndromic basal cell carcinoma. Methods: Literature review in the main databases NCBI-GTR, ClinVar, ClinGen, MedGen, OMIM and GeneReviews, using as descriptors: "BCC" and "basal cell carcinoma". Inclusion criteria: Portuguese or EnGLIsh language, articles on sporadic BCC. Results: Thirteen articles were selected for analysis. The analysis revealed a robust hedgehog pathway link in the genesis of sporadic basal cell carcinoma, with the main genes involved represented by PATCH1, PATCH2 and smoothened. The variants with the highest clinical significance were SMO-M2, PTCH1 and PTCH2-Δ22. The mutation most found was related to the action of UVB, being represented by the substitution of C>T or CC>TT at the pyrimidine site, both in PTCH and in SMO. Conclusion: Extremely important to professionals working in the diagnosis and treatment of BCC, including plastic surgeons, as this way they can better conduct their cases, with more accurate diagnoses and prevention approaches based on the individual susceptibility of each patient, as well as targeted therapies and individualized with better success rates.